(untitled) (Chemical Engineering Research Bulletin, 2011)
The cation exchange chromatographic separation of pyridine, monoethanol and triethanol amines have been explored from source to receiving phase through the fiber supported solid membrane. The fibers supported solid membranes were prepared by chemically modification of cellulose fibers with introducing the carboxylic acid ion exchanging groups. The experimental variables explored were concentration of pyridine, monoethanol and triethanol amines (10 -2 to 10-6 M) in the source solution, HCl (0.01 to 0.20 M) in the receiving phase and stirring speed (50-130 rpm) of the bulk source and receiving phase. The efficiency has been evaluated of fiber supported solid membrane system for the transport of pyridine, monoethanol and triethanol amines from the source solution to receiving phase through the fiber supported solid membrane. The pre-concentration was studied of pyridine, monoethanol and triethanol amines from the dilute solutions. Key words: Pyridine, monoethanol and triethanol amines, fiber supported solid membrane; ion exchange DOI: http://dx.doi.org/10.3329/cerb.v15i1.6788 Chemical Engineering Research Bulletin 15 (2011) 25-29